Faktor Risiko Gangguan Mental Emosional pada Prajurit TNI AD Kodam Iskandar Muda - Mawaddah, Husnul; Abdullah, Asnawi; Marthoenis, M.; Zahara, Meutia; Zakaria, Radhiah (Jurnal Kesehatan Komunitas, 2025)
The problem of mental disorders among soldiers is rarely discussed compared to similar problems among civilians. One form of mental disorder that is often found among soldiers is post-traumatic stress disorder or PTSD. This research aims to determine the risk factors for emotional mental disorders in TNI AD soldiers at the Iskandar Muda Military Command.  This research is observational analytic using a cross sectional design. The population and sample are all TNI AD soldiers registered in the Iskandar Muda Regional Military Command Rikkeswa who had their health checked in 2021 and 2022 totaling 1047 people. This research uses secondary data. The data obtained were analyzed using logistic regression and linear regression tests.The research results showed that risk factors associated with emotional mental disorders in TNI AD soldiers at the Iskandar Muda Military Command were the SGOT enzyme (p= 0.018), body mass index (BMI) value (p= 0.002). and diastolic blood pressure (p= 0.029). Multivariate analysis of BMI value (p = 0.014) was the factor most associated with emotional mental disorders. The variable most associated with emotional mental disorders was BMI (p = 0.014). It is necessary to carry out a strategic action plan to reduce emotional mental disorders related to blood pressure, SGOT enzymes and BMI. Further research needs to be carried out to detect emotional mental disorders in the TNI.